Silicon carbide and related materials 2014 : selected peer reviewed papers from the European Conference on Silicon Carbide & Related Materials (ECSCRM 2014), September 21-25, 2014, Grenoble, France - Chaussende, Didier; Ferro, Gabriel (Materials science forum, 2015)
Collection of selected, peer reviewed papers from the European Conference on Silicon Carbide & Related Materials (ECSCRM 2014), September 21-25, 2014, Grenoble, France. The 243 papers are grouped as follows: I. SiC Growth; I.1 Bulk Growth; I.2 Epitaxial and Thin Film Growth; II. SiC Theory and Characterization; II. 1 Fundamental and Material Properties; II. 2 Point and Extended Defects; II. 3 Surfaces and Interfaces; III. SiC Processing; III. 1 Doping, Implantation and Contact; III. 2 Dielectric Growth and Characterization; III. 3 Etching and Machining; IV. SiC Devices; IV. 1 Diodes; IV. 2 Field Effect Transistors; IV. 3 Other Devices; V. Related Materials; V.1 Other Carbon Based Materials; V.2 Nitrides and Other Materials Keyword: Silicon carbide, Wide bandgap semiconductor, Bulk growth, Epitaxial growth, Processing, Power electronics, MOS, characterization, graphene This volume collects 243 papers from the 10th European Conference on Silicon Carbide & Related Materials (ECSCRM 2014), held in Grenoble, France, in September 2014, where researchers discussed issues in the field of wide bandgap semiconductors, focusing on silicon carbide, but also III-nitrides, diamond, and related materials like graphene. The papers address silicon carbide growth, including bulk, epitaxial, and thin film growth; theory and characterization, including fundamentals and material properties, point and extended defects, and surfaces and interfaces; processing, focusing on doping, implantation, and contact, dielectric growth and characterization, and etching and machining; devices and circuits, such as diodes and field effect transistors; and related materials, including other carbide-based materials and nitrides. Contributors are materials scientists and other researchers from around the world. -- Carbon-- Engineering-- Materials science.